The Secondary Component of the Extremely Low Mass Ratio Massive Binary HD 165246 Revealed by GHOST - C. N. Rodriguez; T. Ansin; G. A. Ferrero; O. G. Benvenuto; R. Gamen; N. I. Morrell; J. I. Arias; R. E. Higa; C. Putkuri; C. Johnston; K. Chiboucas; E. Deibert; et al. (The Astrophysical Journal)
In the pursuit of understanding the multiplicity of massive stars, the OWN Survey has undertaken spectroscopic monitoring of hundreds of targets over the past 20 yr. This effort has led to the discovery of new single-lined spectroscopic binaries. Characterizing the unseen companions of these systems is crucial to deriving precise stellar parameters, including the mass of each component, and constraining formation models for massive binary systems. In this paper, we aim to physically and evolutionarily characterize the stellar components of the massive binary HD 165246. We analyzed spectra obtained by the OWN Survey and used Kepler's second mission (K2) photometry, from which we determined the physical parameters of the system. Thanks to the high-resolution capabilities of the new echelle spectrograph Gemini/GHOST, we could directly detect spectral features of the secondary component for the first time. A very low mass ratio for the system is confirmed ( q  ~ 0.16), making this binary one of the few extremely low mass ratio systems known. The primary star has a mass of M _a  = 22 ± 1 M _⊙ and a radius of R _a  = 7.0 ± 0.1 R _⊙ , while the secondary star has a mass of M _b  = 3.4 ± 0.1 M _⊙ and a radius of R _b  = 2.22 ± 0.02 R _⊙ . Stellar evolution models indicate that the system has undergone approximately two million years of evolution since its formation. Moreover, the secondary star is identified as a pre-main-sequence object, progressing toward the zero-age main sequence. This paper illustrates the power of high-resolution spectrographs such as GHOST in finding much lower mass, previously unseen stellar components of binary star systems.